Caffeine and performance over consecutive days of simulated competition - Stadtheim, H. K.; Spencer, M.; Olsen, R.; Jensen, J. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Performance improvements after caffeine (CAF) ingestion are well documented when using a 1-d protocol. In numerous competitions such as the Tour de France, Tour de Ski, world championships, and National College Athletic Association championships, athletes compete for several days in a row. To date, no studies have investigated the effects of CAF when competing for consecutive days in a row. This study aimed to investigate the effects of placebo (PLA) and two different CAF doses (3 and 4.5 mg·kg-1 body mass) on performance in a 10-min all-out, cross-country, double poling ergometer test (C-PT) 2 d in a row.